Kualitas Organoleptik dan Kadar Kalsium Larutan Kumur Ekstrak Siwak (Salvadora persica) dengan Penambahan Ekstrak Jeruk Purut dan Stroberi - Wijayanti, 'Azizah Fita, Dra. Aminah Asngad, M.Si (2015)
Siwak is known to contain essential oils and various other chemical compounds, such as, alkaloids (salvodorine), vitamin C, chloride, calcium, a large amount of fluoride, silica and sulfur that are beneficial for healthy teeth, gums, and mouth. Strawberries (Fragaria x ananassa) and kaffir lime (Citrus hystrix) is an ingredients that can be blended in the manufacture of mouth rinses, because besides containing vitamin C also contains calcium. The purpose of this study was to determine the organoleptic quality and content of calcium contained in mouth rinses miswakstem extract with the addition of fruit extracts and fruit extracts strawberry lime. The method used in this research is completely randomized design (CRD) factorial with 2 factors, the first factor additional types of materials: strawberry extract (S), extract lime (J), and the second dose of the addition of materials: 40% (D1), 20% (D2), with the volume ratio extracts and miswak material addition 1:1. The highest calcium levels of mouthwash siwak extract with the addition of lime extract 40% (JD1) is 0.0786%. The results showed that there are different calcium content in mouth rinses of extract stem extract siwak with the addition of lime and strawberry fruit extract with different concentrations.